15-Month-Old Infants Fast Map Words but Not Representational Gestures of Multimodal Labels - Puccini, Daniel; Liszkowski, Ulf (Frontiers in Psychology, 2012)
This study investigated whether 15-month-old infants fast map multimodal labels, and, when given the choice of two modalities, whether they preferentially fast map one better than the other. Sixty 15-month-old infants watched films where an actress repeatedly and ostensively labeled two novel objects using a spoken word along with a representational gesture. In the test phase, infants were assigned to one of three conditions: Word, Word + Gesture, or Gesture. The objects appeared in a shelf next to the experimenter and, depending on the condition, infants were prompted with either a word, a gesture, or a multimodal word-gesture combination. Using an infant eye tracker, we determined whether infants made the correct mappings. Results revealed that only infants in the Word condition had learned the novel object labels. When the representational gesture was presented alone or when the verbal label was accompanied by a representational gesture, infants did not succeed in making the correct mappings. Results reveal that 15-month-old infants do not benefit from multimodal labeling and that they prefer words over representational gestures as object labels in multimodal utterances. Findings put into question the role of multimodal labeling in early language development.